Particle acceleration and magnetic fields of relativistic jets through multi-wavelength analyses - Jormanainen, Jenni (fi=Turun yliopisto|en=University of Turku|, 2025)
Relativistic jets launched by supermassive black holes (SMBH) are some of the most extreme phenomena in the Universe. They are best observed in blazars, where the jet is pointing almost directly towards us. This unique alignment means that the jet dominates their observed emission, making them excellent sources for studying the jet properties. This thesis focusses on understanding the particle acceleration in blazar jets and how it is tied to their magnetic felds. Multi-wavelength (MWL) data from four blazars are analysed using various methods. Particle acceleration mechanisms are also explored through magnetic reconnection simulations in the case of one source. Brightness variations of blazars can be observed across the entire electromagnetic spectrum on timescales of years down to minutes. In the past, shocks have been shown to describe blazar faring well, and the MWL polarisation data analysed from one blazar (Mrk 501) as part of this thesis supports this scenario. At the same time, minute-scale fares in the very high-energy (VHE, > 100 GeV) gamma rays are diffcult to explain with shocks. Magnetic reconnection from a small region could provide a solution to this. Magnetic reconnection simulations are tested in the case of Mrk 421, and they are found to reproduce the observed VHE faring. The co-existence of two different acceleration mechanisms can be possible if there are several emitting regions within the jet. The broad-band spectrum of one source (VER J0521+211) is modelled, and the high energy emission is found to orig¬inate from a smaller region closer to the SMBH where also magnetic reconnection could take place. In the same study, modelling of the long-term optical polarisation supports the need for several components to produce the observed polarisation. An analysis of MWL polarisation observation together with very long baseline interferometry data is used to track a moving jet component passing through a sta¬tionary shocked region of the jet of OJ 287. The passage also coincides with a VHE fare, hinting at their connection. The studies included in this thesis provide important clues for solving the open questions related to particle acceleration and the magnetic felds in blazar jets.